The country pancake - Fine, Anne (London : Egmont, 2002)
Like an angel, Miss Mirabelle stepped into the lives of the children of Wallisdean Park School. Enchanting she may be, but Miss Mirabelle still ends up in big trouble.
Keywords: Children's stories; Fiction